The Implementation of Digital Marketing in Culinary Businesses in Kebonsari - Jember: Penerapan Digital Marketing pada Usaha Kuliner di Kebonsari - Jember - Tiffany Rahma Abdillah; Supriono, Agus; Setyawati, Intan Kartika; Hariyono, Kacung; Sunartomo, Aryo Fajar; Putri, Maharani Karunia (Fakultas Ilmu Komputer, Universitas Jember, 2025)
With the rapid development of technology, the business world has now entered digital marketing, often referred to as digital marketing. This marketing utilizes social media and internet-based platforms to market products. One of the economic strengths that has been supporting the Indonesian economy is the presence of Micro, Small, and Medium Enterprises (MSMEs). The implementation of digital marketing opens up significant opportunities for MSMEs to capitalize on it. Culinary MSMEs in Kebonsari Village, Jember Regency, East Java, are experiencing challenges in running their businesses, particularly in marketing, which has previously been carried out only through conventional methods. Therefore, training is needed on the use of digital marketing and the creation of engaging content. The goal of this activity is to provide knowledge about the importance of digital marketing in product marketing and how to create creative content to build product branding. Digital marketing can be implemented using social media platforms like Instagram and online platforms like Grab (Grabfood) and Gojek (Gofood). Community service activities are carried out for one month with a different agenda each week. The stages carried out include (1) Location survey and identification of problems experienced, (2) Training in the use of social media and training in taking photos/videos, (3) Assistance in the use of social media and training in taking photos/videos and (4) Monitoring and evaluation of activities. The results of these activities are (1) Problems were found, namely a decrease in sales turnover of culinary businesses because marketing so far still uses conventional methods, (2) Culinary MSME actors know and apply digital marketing by using social media Instagram and online platforms such as Grab (Grabfood) and Gojek (Gofood), (3) Culinary MSME actors have expertise in taking photos/videos as promotional media. With this training activity, culinary MSME actors as the target of the activity feel helped because with this program they can understand what digital marketing is and how to implement it.